Exosomal miRNA-19b-3p of tubular epithelial cells promotes M1 macrophage activation in kidney injury - Lv, Lin-Li; Feng, Ye; Wu, Min; Wang, Bin; Li, Zuo-Lin; Zhong, Xin; Wu, Wei-Jun; Chen, Jun; Ni, Hai-Feng; Tang, Tao-Tao; Tang, Ri-Ning; Lan, Hui-Yao; et al. (Cell death and differentiation, 2020)
Tubulointerstitial inflammation is a common characteristic of acute and chronic kidney injury. However, the mechanism by which the initial injury of tubular epithelial cells (TECs) drives interstitial inflammation remains unclear. This paper aims to explore the role of exosomal miRNAs derived from TECs in the development of tubulointerstitial inflammation. Global microRNA(miRNA) expression profiling of renal exosomes was examined in a LPS induced acute kidney injury (AKI) mouse model and miR-19b-3p was identified as the miRNA that was most notably increased in TEC-derived exosomes compared to controls. Similar results were also found in an adriamycin (ADR) induced chronic proteinuric kidney disease model in which exosomal miR-19b-3p was markedly released. Interestingly, once released, TEC-derived exosomal miR-19b-3p was internalized by macrophages, leading to M1 phenotype polarization through targeting NF-κB/SOCS-1. A dual-luciferase reporter assay confirmed that SOCS-1 was the direct target of miR-19b-3p. Importantly, the pathogenic role of exosomal miR-19b-3p in initiating renal inflammation was revealed by the ability of adoptively transferred of purified TEC-derived exosomes to cause tubulointerstitial inflammation in mice, which was reversed by inhibition of miR-19b-3p. Clinically, high levels of miR-19b-3p were found in urinary exosomes and were correlated with the severity of tubulointerstitial inflammation in patients with diabetic nephropathy. Thus, our studies demonstrated that exosomal miR-19b-3p mediated the communication between injured TECs and macrophages, leading to M1 macrophage activation. The exosome/miR-19b-3p/SOCS1 axis played a critical pathologic role in tubulointerstitial inflammation, representing a new therapeutic target for kidney disease.